Wing trait–inversion associations in Drosophila subobscura can be generalized within continents, but may change through time. (12th October 2015) - Simões, P.; Fragata, I.; Lopes‐Cunha, M.; Lima, M.; Kellen, B.; Bárbaro, M.; Santos, M.; Matos, M.
Abstract: Clinal variation is one of the most emblematic examples of the action of natural selection at a wide geographical range. In Drosophila subobscura, parallel clines in body size and inversions, but not in wing shape, were found in Europe and South and North America. Previous work has shown that a bottleneck effect might be largely responsible for differences in wing trait–inversion association between one European and one South American population. One question still unaddressed is whether the associations found before are present across other populations of the European and South American clines. Another open question is whether evolutionary dynamics in a new environment can lead to relevant changes in wing traits–inversion association. To analyse geographical variation in these associations, we characterized three recently laboratory founded D. subobscura populations from both the European and South American latitudinal clines. To address temporal variation, we also characterized the association at a later generation in the European populations. We found that wing size and shape associations can be generalized across populations of the same continent, but may change through time for wing size. The observed temporal changes are probably due to changes in the genetic content of inversions, derived from adaptation to the new, laboratory environment. Finally, we show that it is not possible to predict clinal variation from intrapopulation associations. All in all this suggests that, at least in the present, wing traits–inversion associations are not responsible for the maintenance of the latitudinal clines in wing shape and size.